New partnerships, new perspectives: The relevance of sexual and reproductive health and rights for sustainable development - Mayhew, Susannah H.; Newman, Karen; Johnson, David; Clarkd, Emily; Hammere, Michael; Mohand, Vik; Ssali, Sarah (Health Policy, 2019)
In the light of the opportunities presented by the Sustainable Development Goals (SDGs) debate is being reignited to understand the connections between human population dynamics (including rapid population growth) and sustainable development. Sustainable development is seriously affected by human population dynamics yet programme planners too often fail to consider them in development programming, casting doubt on the sustainability of such programming. Some innovative initiative sare attempting to cross sector boundaries once again, such as the Population Health and Environment(PHE) programmes, which are integrated programmes encompassing family planning service provision with broader public health services and environmental conservation activities. These initiatives take on greater prominence in the context of the SDGs since they explicitly seek to provide cross-sector programming and governance to improve both human and planetary wellbeing. Yet such initiatives remain under-researched and under promoted.
Keywords: Reproductive health; Population; Sustainable development; SDGs; Integrationa